Zwi(ch)nięte koło radykalnohermeneutyczne - Szaj, Patryk (Przestrzenie Teorii, 2019)
The article is an interpretation of the traditional figure of the hermeneutic circle made from the perspective of John D. Caputo’s radical hermeneutics. It begins with a recapitulation of the most important modern positions on the hermeneutic circle, which postmodern hermeneutics radicalizes, noting the impossibility of its closure or fulfillment. Movement in the postmodern hermeneutic circle takes place not between the parts and the whole, but only between the different parts. Thus, one might say that this circle is twisted, and this has a dual meaning. It evokes Jacques Derrida’s interpretation of a phrase from Hamlet, “time is out of joint”, but it also plays with the meaning of the twist, which can be understood as a Verwindung: the impossibility of the transgression beyond modern hermeneutics.